Menentukan Kebutuhan Desain Organisasi Berdasarkan Analisis Strategi Dan Lingkungan Bisnis: Penelitian - Rahmafathi, Dini; Hamzah, Muhamad; Nur Azizah, Nadya; Edward Utama, ⁠Rony (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Organizational design is a fundamental bridge between organization strategy and operational implementation. This research aims to analyze how organizations determine their design needs based on strategic analysis and business environment through three case studies. The method used is descriptive qualitative on PT Telkom Indonesia, SAP Malaysia Consulting Firm, and Social Institutions (GNG, Dompet Dhuafa, Rumah Zakat). The results show that each organization carries out a design transformation from a rigid structure to a more agile, digital, and collaboration-based model. Adjusting the structure following the strategy proved crucial in facing complex environments to achieve competitive advantage.